Multi‐Decadal Carbon Cycle Measurements Indicate Resistance to External Drivers of Change at the Howland Forest AmeriFlux Site. Issue 8 (6th August 2021) - Hollinger, D. Y.; Davidson, E. A.; Fraver, S.; Hughes, H.; Lee, J. T.; Richardson, A. D.; Savage, K.; Sihi, D.; Teets, A.
Abstract: A long‐standing goal of ecology has been to understand the cycling of carbon in forests. This has taken on new urgency with the need to address a rapidly changing climate. Forests serve as long‐term stores for atmospheric CO2, but their continued ability to take up new carbon is dependent on future changes in climate and other factors such as age. We have been measuring many aspects of carbon cycling at an unmanaged evergreen forest in central Maine, USA, for over 25 years. Here we use these data to address questions about the magnitude and control of carbon fluxes and quantify flows and uncertainties between the different pools. A key issue was to assess whether recent climate change and an aging tree population were reducing annual C storage. Total ecosystem C stocks determined from inventory and quantitative soil pits were about 23, 300 g C m −2 with 46% in live trees, and 48% in the soil. Annual biomass increment in trees at Howland Forest averaged 161 ± 23 g C m −2 yr −1, not significantly different from annual net ecosystem production (NEP = −NEE) of 211 ± 40 g C m −2 y −1 measured by eddy covariance. Unexpectedly, there was a small but significant trend of increasing C uptake through time in the eddy flux data. This was despite the period of record including some of the most climate‐extreme years in the last 125. We find a surprising lack of influence of climate variability on annual carbon storage in this mature forest. Plain Language Summary: Trees remove carbon dioxide (CO2 ) from the atmosphere by photosynthesis and store it in chemical form in wood and other plant tissues. Much of the stored carbon ends up in the soil. Plants and soil organisms use some of the stored carbon to provide energy for growth and plant maintenance processes which releases CO2 back to the atmosphere. The movement of carbon atoms into and out of the forest and through the plants and soils is termed the "carbon cycle". We have been studying the carbon cycle of the Howland Forest in central Maine, an unmanaged evergreen forest with most trees between 100 and 200 years old. Over the last 25 years the forest has stored almost 3.5 tons of CO2 per acre each year, even though that timespan has included the warmest, wettest, and driest years in the last 125. Although the forest is maturing, it is storing on average a bit more carbon each year and there is as yet no clear reason why. Forest growth is a natural solution to the problem of too much CO2 in the atmosphere. This research helps show the longer‐term stability and viability of forests as natural climate solutions. Key Points: An unmanaged evergreen forest has been a net carbon sink for over 25 years and the sink strength has increased significantly with time Annual average carbon increment measured by eddy flux or inventory data are not significantly different The forest remained a robust C sink in the warmest, wettest, and driest years since 1895, indicating resistance to climate variability